2003
DOI: 10.1007/bf03027194
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ca addition on the oxidation resistance of AZ91 magnesium alloys at elevated temperatures

Abstract: AZ91 magnesium alloys containing 0.27-5.22 wt.% Ca, were melted and cast to study the effects of Ca addition on oxidation resistance at elevated temperatures. An ignition temperature test showed that the ignition of AZ91 alloy occurred at about 350-450°C below the melting point, whereas that of the Ca-containing AZ91 alloys did so at above 650°C. Weight gain measurements indicated that the oxidation resistance of the AZ91 alloys improved with Ca addition. The oxidation rate was dependent on the oxidation tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
25
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(25 citation statements)
references
References 5 publications
0
25
0
Order By: Relevance
“…4,5) In these studies, the inner layer was either a mixture of (MgO, CaO) in the case of Mg + (0:5$3) mass% Ca alloys, 4) or a mixture of (MgO, CaO, Al 2 O 3 ) in the case of AZ91 + (0:3$5) mass% Ca alloys. 5) AZ91D is the Al-rich, high-strength cast Mg alloy that is most widely used.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) In these studies, the inner layer was either a mixture of (MgO, CaO) in the case of Mg + (0:5$3) mass% Ca alloys, 4) or a mixture of (MgO, CaO, Al 2 O 3 ) in the case of AZ91 + (0:3$5) mass% Ca alloys. 5) AZ91D is the Al-rich, high-strength cast Mg alloy that is most widely used.…”
Section: Introductionmentioning
confidence: 99%
“…While the understanding of these Ca containing alloys, in terms of oxidation and casting behaviour, has vastly increased in the recent years [18,19,20], their forming capabilities on the other hand have not yet been in the focus of intense investigations. Those investigations are necessary if this promising alloy system is to be employed in industrial applications.…”
Section: Introductionmentioning
confidence: 99%
“…Fan et al [3] studied the combined addition of Y and Ce into pure Mg and found that some Mg-Y-Ce alloys could melt safely at 1173 K in air without any protection. Choi et al [4] investigated the effect of Ca addition on oxidation resistance of AZ91 Mg alloy at elevated temperatures and proved that the oxidation rate of Ca-containing AZ91Mg alloys decreased significantly. Among these ignition-proof alloying elements, Ca is thought to be more suitable than others, on account of its low density, extensive source and nontoxicity.…”
Section: Introductionmentioning
confidence: 99%